MILITARY METAPHORS AS MEANS OF POLITICAL VALIDITY REPRESENTATION IN YULIA TYMOSHENKO'S IDIOSTYLE - K. A. Kovaleva (Вестник Кемеровского государственного университета, 2013)
The paper represents a research of metaphors as cognitive mechanisms. The specific character of military metaphors and their role in conceptualization of Ukraine’spolitical life in Yulia Tymoshenko’sidiostyleare considered. The astable political situation in Ukraine in XXI century, and Yulia Tymoshenko struggling against her opponents during a major part of her political career cause a special efficiency of such metaphors in her political speeches.The frames structuring the given metaphor are consistently described, the lexical units included in the metaphoric representation are established, the bases of metaphorical shift are defined. The author concludes that the most frequent and structured metaphorsin Yulia Tymoshenko’s speeches are thosewith area-source of "war", the widely presented frames being those of «War and its versions», «Organization of military service», «Military actions and arms», «Beginning of war and its results». Such metaphors reveal the concern for the country’s fate, aspiration to struggle for the sake of its best future and to win for the good of Ukraine.